Meningkatkan Hasil Belajar Siswa Melalui Model Project Based Learning Pada Materi Jaring-Jaring Bangun Ruang Di Kelas V SDN Lamsayuen Aceh Besar - Widya Utami; Fauzi Fauzi; Ahadin Ahadin (Universitas Syiah Kuala, 2023)
Abstract The material for spatial networks is considered material that is challenging for understudies to comprehend. How understudies might interpret the material of spatial structure nets is still low, so a learning model methodology is required to have been ready to work on’s how understudies might interpret the material or mathematical nets. The formulation of the problem in this research is how to increase the activities of teacher, students, and student learning outcomes through the Project Based Learning (PjBL) model on the material of building space nets in class V SDN Lamsayuen Aceh Besar. This study aims to increase the activities of teachers, students, and to find out student learning outcomes through the Project Based Learning (PjBL) model on the material of building space nets at SDN Lamsayuen Aceh Besar. The subjects in this study were 29 students, 15 male students adn 14 female students. The data analysis technique used is observation and test. Data analysis used descriptive qualitative analysis using the percentage formula. The results of observations showed that there was an increase in teacher activity in the first cycle the average value was 3,25 (enough), in the second cycle the avarage value was 4,25 (good) and in the third cycle the average value was 4,75 (very good). the student activity in the first cycle has an average score or 2,95 (enough), in the secon cycle the average value is 3,85 (good) and in the third cycle the avarage value is 4,32 (good). Learning outcomes in the first cycle the average value is 65,8 with 31% classical completeness, in the second cycle the average value is 75,3 with 72,4% classical completeness and the third cycle the average value is 81 with 86% classical completeness.